PEMAKAIAN BAHASA GAUL DAN KESANTUNAN BERBAHASA PADA MAHASISWA UNIKA WIDYA MANDALA MADIUN - Diani Febriasari (Humaniora Scientia, 2014)
The problems of the research are the use of pop language and language manner used by the students of Catholic University of Widya Mandala Madiun. The writer applies qualitative method in analyzing the data. The data were taken from the studentsâ€™ expression in facebook and analyzed according to the topic, atmosphere, venue, and interlocutor. Based on the research, the writer found 131 words of pop language which were spoken by the students of Catholic University of Widya Mandala Madiun . The words of pop language were grouped according to abbreviation, head word, complex word, predication, acronym, vocabulary, and phoneme omission. The writer acknowledged 10 violation of language manner done by the students of Catholic University of Widya Mandala University. The violations consisted of 2 violations of wisdom of maxim, 1 violation of generosity maxim, 1 violation of appraisal maxim, 3 violations of humility maxim, 1 violation of agreement maxim, and 2Â  violations of sympathy maxim. The violations occurred because there were humorous substances caused by the intimacy among the users of facebook and deliberateness caused by a desire for bringing down others. Key word: pop language, language manner